Silver Thin‐Film Electrodes Grown by Low‐Temperature Plasma‐Enhanced Spatial Atomic Layer Deposition at Atmospheric Pressure. Issue 1 (10th October 2022) - Hasselmann, Tim; Misimi, Bujamin; Boysen, Nils; Zanders, David; Wree, Jan‐Lucas; Rogalla, Detlef; Haeger, Tobias; Zimmermann, Florian; Brinkmann, Kai Oliver; Schädler, Sebastian; Theirich, Detlef; Heiderhoff, Ralf; et al.
Abstract: The unique properties of atomic layer deposition (ALD) are mainly exploited for metal oxides, while the growth of metals, such as silver, is still in its infancy. Low growth temperatures and high growth rates are essential to achieve conductive (i.e. percolated) films. Here, a study based on the authors' recently introduced N ‐heterocyclic carbene‐based Ag amide precursor [(NHC)Ag(hmds)] (1, 3‐di‐tert‐butyl‐imidazolin‐2‐ylidene silver(I) 1, 1, 1‐trimethyl‐ N ‐(trimethylsilyl) silanaminide) using plasma‐enhanced spatial ALD at atmospheric pressure and at deposition temperatures as low as 60 °C, is provided. The favorable reactivity and high volatility of the [(NHC)Ag(hmds)] precursor affords high growth rates up to 3.4 × 10 14 Ag atoms cm –2 per cycle, which are ≈2.5 times higher than that found with the established triethylphosphine(6, 6, 7, 7, 8, 8, 8‐heptafluoro‐2, 2‐dimethyl‐3, 5‐octanedionate) silver(I) [Ag(fod)(PEt3 )] precursor. Consequently, highly conductive Ag films with resistivities as low as 2.7 µΩ cm are achieved at a deposition temperature of 100 °C with a percolation threshold of ≈2.6 × 10 17 Ag atoms cm –2, which is more than 1.6 times lower compared to [Ag(fod)(PEt3 )]. As a concept study, conductive Ag layers are used as bottom electrodes in organic solar cells, that achieve the same performance as those based on Ag electrodes resulting from a high vacuum process. Abstract : The deposition of Ag thin films by low temperature plasma‐enhanced spatial atomic layer deposition at atmopsheric pressure (APP‐SALD) using a novel N‐heterocyclic carbene‐based Ag amide precursor [(NHC)Ag(hmds)] is studied. Percolated and conductive layers are achieved in the temperature range from 60 to 120 °C. In a case study, these layers are used as bottom electrodes for efficient organic solar cells.